Assemblages of health: Deleuze's empiricism and the ethology of life - Duff, Cameron (2014)
© 2014 Springer Science+Business Media Dordrecht. All rights are reserved. This book presents a review of Deleuze's key methods and concepts in the course of exploring how these methods may be applied in contemporary studies of health and illness. Taken from a Deleuzian perspective, health and wellbeing will be characterized as a discontinuous process of affective and relational transitions. The book argues that health, conceived in terms of the quality of life, is advanced or facilitated in the provision of new affective sensitivities and new relational capacities. Following an assessment of Deleuze's key ideas, the book will offer a series of case studies designed to illustrate how Deleuze's ideas can be applied to select health problems. This analysis draws out the specific advantages of a Deleuzian approach to public health research, establishing grounds for more widespread engagement with Deleuze's ideas across the health and social sciences.